2016
DOI: 10.1590/1413-812320152111.18752015
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à autopercepção negativa da saúde entre idosos não institucionalizados de Montes Claros, Brasil

Abstract: This study aimed to obtain an understanding of the self-rated health among community-dwelling elderly people in the north

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
1
33

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 26 publications
6
29
1
33
Order By: Relevance
“…In the present study, older people with a negative self-perception of health and who were frail reported greater difficulties in accessing health services. Similar results were observed in studies conducted in São Paulo 27 and Minas Gerais 28 . A negative perception of health may be related to the presence of morbidity, frailty and other conditions that determine a greater need for medical services.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, older people with a negative self-perception of health and who were frail reported greater difficulties in accessing health services. Similar results were observed in studies conducted in São Paulo 27 and Minas Gerais 28 . A negative perception of health may be related to the presence of morbidity, frailty and other conditions that determine a greater need for medical services.…”
Section: Discussionsupporting
confidence: 90%
“…Desse modo, os resultados da atual investigação alertam para a necessidade de cuidados para com as idosas que possuem IU e que avaliaram negativamente sua própria saúde. Atenção especial deve ser dada ao idoso que não avalia positivamente sua condição de saúde, almejando um melhor manejo das condições crônicas e das incapacidades para promover qualidade de vida e aumento da longevidade 31 . De maneira similar a este trabalho, outros estudos também encontraram associação entre a IU e o relato de artrite, artrose e reumatismo entre as mulheres idosas 26,32 .…”
Section: ▄ Resultadosunclassified
“…Todo esse contexto também pode repercutir negativamente na qualidade de vida do idoso. Assim, é necessário que os profissionais de saúde realizem a identificação oportuna de idosos com maior grau de fragilidade, a fim de que sejam prestados os cuidados mais apropriados 31 . Por fim, embora este inquérito possua um caráter pioneiro no cenário investigado, há limitações que devem ser consideradas.…”
Section: ▄ Resultadosunclassified
“…A explicação para tal resultado é que a saúde percebida pelo idoso está relacionada com a incapacidade e não com serem portadores de doença crônica. Portanto, quanto maior o grau de dependência, maior será a autopercepção como ruim (MEDEIROS et al, 2016).…”
Section: Discussionunclassified